Predictors and clinical outcomes of incomplete hemostasis following transradial coronary intervention: the role of activated clotting time and procedural factors - Shin, Yujin; Lee, Jae Myoung; Yu, Ga-In; Bae, Jae Seok; Cho, Yun-Ho; Jang, Jeong Yoon; Park, Yongwhi; Kwak, Choong Hwan; Kim, Yong-Lee; Kang, Min Gyu; Kim, Kye-Hwan; Park, Jeong Rang; et al. (Frontiers in Medicine, 2025)
BackgroundMajor vascular complications are less frequent with trans-radial artery (TRA) access compared to transfemoral artery access. However, a substantial proportion of patients experience incomplete hemostasis following TRA intervention. This study aimed to identify factors associated with incomplete hemostasis and evaluate the predictive value of pre- and post-procedural activated clotting time (ACT).MethodsA total of 1,241 patients who underwent TRA intervention were included in a prospectively maintained single-center registry. Initial ACT was measured after sheath insertion, and final ACT was measured before sheath removal. Patients were categorized into complete and incomplete hemostasis groups based on achieving complete hemostasis within 2 h of continuous compression.ResultsIncomplete hemostasis occurred in 230 patients (18%). Initial and final ACT values were significantly higher in the incomplete hemostasis group compared to the complete hemostasis group (initial ACT: 146 ± 37 s vs. 136 ± 32 s, p < 0.001; final ACT: 259 ± 85 s vs. 243 ± 72 s, p = 0.015). Multivariate analysis revealed that prolonged initial ACT (OR, 2.41; 95% CI, 1.71–3.39; p < 0.001) and final ACT (OR, 2.25; 95% CI, 1.52–3.30; p < 0.001) were independently significant predictors.ConclusionInitial and final ACT measurements add predictive value to conventional risk factors for incomplete hemostasis in patients undergoing TRA intervention.